Mythologies of Usury in Finance: Analyzing Denotation, Connotation, and Cultural Myth using Roland Barthes' Framework - Bayu Tri Cahya; Nor Aishah Mohd Ali; Dwi Putri Restuti; Dian Nilam Sari; Muslim Marpaung; Rahmat Ilyas (AL-MUZARA'AH, 2026)
This study explores the reality of usury through a semiotic analysis based on Roland Barthes' postmodern study. The research employs a qualitative approach with a postmodernist perspective and includes in-depth interviews with academics and economic practitioners. The study was conducted both in Java and outside Java, Indonesia, involving seven participants, including practitioners and academics. The analysis reveals that usury, as postulated in Barthes' postmodern framework, can be interpreted through denotation, connotation, and myth. Denotatively, usury is seen as an additional charge on a debt at the time of repayment, exploiting debt transactions, adding monetary charges, and imposing burdensome loans on borrowers. Connotatively, usury is viewed as exploitation of borrowers, services that offer loans with high-interest rates, and unfair interest rates that favor financiers. Mythically, usury is interpreted as a revolving loan, the exchange of goods with varying qualities, pawning, and brokerage in projects. The reality of usury, as hidden behind these interpretations, suggests that usury is a form of injustice, an iceberg phenomenon, a dependency, and involves shirkah (partnership) in usury bondage.